Multidisciplinary Management of Pancreatic Adenocarcinoma: Clinical Practice Guideline AUNA - Montenegro Beltrán, Paola (2022)
Introduction: This article provides recommendations for the Multidisciplinary Management of Pancreatic Adenocarcinoma in the RED AUNA. Methods: A systematic search of clinical practice guidelines (CPG) similar to topics of interest was developed, it was assessed with the AGREE II instrument, a list of questions was elaborated under the PICO structure, a de novo search was carried out prioritizing reviews systematic with or without meta-analysis, followed by primary studies, the elaboration of the evidence tables and the evaluation of the global quality for the outcomes of the clinical questions was carried out following the GRADE methodology. Results: 5 PICO questions corresponding to initial management and systemic management were formulated with 18 recommendations regarding the most effective method for pathological diagnosis, biliary drainage and the most effective and safe systemic treatment in the neoadjuvant, adjuvant and metastatic setting. Conclusions: This article summarizes the methodology and evidence-based recommendations of the CPG for the multidisciplinary management of pancreatic adenocarcinoma of the AUNA Clinic Network.